ECONOMICS, POLITICS AND PROSPERITY IN RESTORATION ENGLAND an intellectual history of the works... of Sir William Temple. - HAAVISTO, JUHA (Perspectives in economic and social history, 2025)
Drawing on key published works, as well as those of his contemporaries, this book explores the political and economic thought of the seventeenth-century diplomat William Temple and his proposals for change in Restoration England and Ireland.Adopting a revisionist approach, the book explores Temple's efforts to balance and advance English society during a period of shifting power between England, the Netherlands and France. Engaging with themes including mercantilism, state building and environmental determinism, Temple connected the ideas of antiquity to those of contemporaries while influencing subsequent intellectual currents. As the book shows, Temple viewed humans as curious and greedy creatures, who would stop at nothing unless their motivations and passions could be subdued or diverted. This belief had immediate practical political and economic consequences in Temple's work: the survival and stability of the polity had to be secured, but he also advocated toleration so that members of society were afforded space to follow their motivations. Furthermore, this led Temple to argue that prosperity could be achieved not only by managing human nature but through practical action as well. He advocated for direct investment in Ireland to boost its commercial prospects, albeit for the benefit of the English crown, in a way that foreshadows current thinking on economic development.This book will be of interest to readers in the history of economic and political thought, environmental history, intellectual history and early modern history more broadly.